Observations on variation in the ultrastructure of the proximal testicular ducts of the ground skink, scincella lateralis (reptilia: Squamata). (28th November 2012) - Sever, David M.; Rheubert, Justin L.; Hill, Toren A.; Siegel, Dustin S.
Abstract The North American Ground Skink, Scincella lateralis, is a member of the most speciose family of lizards, the Scincidae. The only descriptions of the testicular ducts of skinks concern the light microscopy of 13 species in eight other genera. We combine histological observations with results from transmission electron microscopy on a sample of skinks collected throughout the active season. The single rete testis has squamous epithelium with a large, indented nucleus and no junctional complexes between cells or conspicuous organelles. Nuclei of sperm in the rete testis area are associated with cytoplasmic bodies that are lost in the ductuli efferentes. The ductuli efferentes have both ciliated and nonciliated cells and show little seasonal variation except for the narrowing of intercellular canaliculi when sperm are absent. When the ductus epididymis contains sperm, the anterior one‐third lacks copious secretory material around luminal sperm, whereas in the posterior two‐thirds sperm are embedded in a dense matrix of secretory material. Light and dark principal cells exist and both contain saccular, often distended rough endoplasmic reticula, and widened intercellular canaliculi that bridge intracellular spaces. Junctional complexes are lacking between principal cells except for apical tight junctions. Electron‐dense secretory granules coalesce at the luminal border for apocrine release. The cranial end of the ductus deferens is similar in cytology to the posterior ductus epididymis. Each of the nine squamates in which the proximal testicular ducts have been studied with electron microscopy has some unique characters, but no synapomorphies for squamates as a group are recognized. J. Morphol., 2013. © 2012Wiley Periodicals, Inc.